S55 The Aminopeptidase CD13 Regulates Homotypic Aggregation of Neutrophils. (19th November 2012) - Fiddler, CA; Murphy, G; Cowburn, AS; Parfrey, H; Chilvers, ER
Abstract : Neutrophils are critical effector cells of the innate immune response and are recruited to sites of tissue injury in response to locally generated chemoattractants. Neutrophil recruitment is a highly regulated process involving complex interactions with the vascular endothelium and underlying tissue stroma. In addition to adhering to the endothelium, neutrophils can also self-associate, (a process known as homotypic aggregation - HA), which has been proposed to play a key role in disease states such as sepsis. Aminopepetidase N or CD13 is a widely expressed membrane-bound metallopeptidase involved in the migration and invasion of cancer and endothelial cells. Neutrophils express CD13 on their cell surface, which is upregulated by TNF-α, IL-8 and fMLP We have shown that inhibition of aminopeptidase activity enhances the efficacy of TNF-α-induced neutrophil apoptosis (Cowburn et al. J Biol Chem 2006; 281:12458). Cross-linking anti-CD13 monoclonal antibodies (mAb) have been shown to induce HA of monocytic cells through PI3K activation (Mina-Osorio et al. J Leuk Biol 2006; 79:719). We hypothesised that CD13 may be involved in neutrophil migration and HA. Using plasma-Percoll purified human neutrophils and a modified Boyden filtre assay we showed that IL-8 mediated neutrophil chemotaxis was not affected by either the CD13 mAb WM-15 or the aminopeptidase enzymatic inhibitor bestatin. In contrast, IL-8-mediated neutrophil migration through type 1 collagen gels was significantly impaired by WM-15 and MY7 mAbs, which both inhibit enzymatic activity and induce clustering of CD13. The non-clustering CD13 antibody WM-47 and bestatin had no effect. WM-15 and MY7 also promoted neutrophil aggregation as assessed by light microscopy. Phase-contrast video-microscopy demonstrated that in WM-15 treated neutrophils, where HA was evident, the percentage of cells entering collagen 1 gels in response to IL-8 was significantly reduced (26.9% vs 71.8% in non-HA cells). WM-15 does not prime neutrophils, as assessed by superoxide production and shape change, and the cell surface expression of CD11b, CD18 and CD66b were not altered. These data suggest a novel role for CD13 in the homotypic aggregation of neutrophils, which reduces chemoattractant-induced migration through collagen 1 matrix and may predispose to neutrophil micro-aggregation within the circulation.